Spatial photocontrol of the passive optical output direction of the elastic molecular crystals based on acylhydrazone derivatives. (October 2021) - Peng, Jiang; Xing, Jingliang; Bai, Jiakun; Ren, Ying; Wang, Tao; Jia, Junhui
Abstract: The photo-reactive acylhydrazone derivatives (4-FBAc, 4-ClBAc, 4-BrBAc and 4-IBAc ) had been prepared, and they could undergo reversible E - Z isomerization reactions in the crystals under UV (365 nm) irradiation and heating condition. Meanwhile, the significant photomechanical behaviors were observed for the crystals with different shapes. The crystals of 4-FBAc (block-like), 4-ClBAc (block-like) and 4-BrBAc (rod-like) showed light-induced cracking, salient and cracking behaviors, respectively. Interestingly, the crystals of 4-FBAc (needle-like) and 4-IBAc (needle-like) bent away from the UV light ( E → Z isomerization) firstly, then bent toward the source with the increasing of the irradiation or heating time (structure relaxation and Z → E isomerization). The theoretical study also showed that the molecules could undergo reversible E - Z isomerization reactions under UV irradiation and heating condition. Interestingly, the passive optical (635 nm) output direction of the crystal of 4-FBAc could be controlled by UV light. When mechanical force was applied or removed, the needle-like crystals of 4-FBAc and 4-IBAc exhibited reversible elastic bending properties. Analysis of the single crystal data suggested that C–H⋯π and H-bonds were responsible for the flexibility. So, the elastic organic molecular crystals based on acylhydrazone derivatives could be used as the candidate for crystal actuators and position-controllable optical transducer. Graphical abstract: Image 1 Highlights: Upon UV irradiation, the crystals of 4-FBAc, 4-ClBAc, 4-BrBAc and 4-IBAc showed obvious macroscopic movements. Needle-like crystals of 4-FBAc and 4-IBAc exhibited reversible elastic bending upon applying and releasing of the stress. The output direction of passive light transmission could be controlled by UV light.